Identification of Xenopus SMC protein complexes required for sister chromatid cohesion - Losada, Ana (Cold Spring Harbor Laboratory Press, 1998)
The structural maintenance of chromosomes (SMC) family is a growing family of chromosomal ATPases. The founding class of SMC protein complexes, condensins, plays a central role in mitotic chromosome condensation. We report here a new class of SMC protein complexes containing XSMC1 and XSMC3, Xenopus homologs of yeast Smc1p and Smc3p, respectively. The protein complexes (termed cohesins) exist as two major forms with sedimentation coefficients of 9S and 14S. 9S cohesin is a heterodimer of XSMC1 and XSMC3, whereas 14S cohesin contains three additional subunits. One of them has been identified as a Xenopus homolog of the Schizosaccharomyces pombe Rad21p implicated in DNA repair and the Saccharomyces cerevisiae Scc1p/Mcd1p implicated in sister chromatid cohesion. 14S cohesin binds to interphase chromatin independently of DNA replication and dissociates from it at the onset of mitosis. Immunodepletion of cohesins during interphase causes defects in sister chromatid cohesion in subsequent mitosis, whereas condensation is unaffected. These results suggest that proper assembly of mitotic chromosomes is regulated by two distinct classes of SMC protein complexes, cohesins and condensins.